Amyloid and tau‐driven signatures in hippocampal GFAP‐positive astrocytes. (20th December 2022) - Bellaver, Bruna; De Bastiani, Marco Antônio; Brum, Wagner S.; Ferreira, Pamela C.L.; Povala, Guilherme; da Rocha, Andreia Silva; Ferrari‐Souza, João Pedro; de Souza, Débora Guerini; Karikari, Thomas K; Rosa‐Neto, Pedro; Pascoal, Tharick A; Zimmer, Eduardo R
Abstract: Background: Despite the known heterogeneity of astrocyte responses to injuries, Alzheimer's disease (AD) pre‐clinical and clinical research relies on the glial fibrillary acidic protein (GFAP) as a proxy of astrocyte reactivity. Recently, it was demonstrated that plasma GFAP levels differentially relate to AD hallmarks, associating with amyloid‐β (Aβ), but not with tau pathology. However, the molecular underpinnings behind this specificity are still unexplored. Here, we aim to uncover the molecular signatures of GFAP‐positive astrocytes driven by either by Aβ or tau pathology. Method: Hippocampal GFAP‐positive astrocytes data from 6 month‐old TauP301S ( n = 5), 11.5 months‐old APP/PS2 ( n = 5) and their wild‐type littermates (WT, n = 5) were acquired from GEO datasets (GSE129770;GSE129797) and used to identify differentially expressed genes (DEGs) and enriched biological processes. DEGs were evaluated using the DESeq2 method. Further data analysis included Gene Ontology (GO) functional evaluation. Result: Principal component analysis clearly differentiated gene expression of GFAP‐positive astrocytes from APP/PS2, TauP301S and their WT controls (Fig.1A ). Interestingly, only 30 DEGs overlapped among GFAP‐positive astrocytes from these two transgenic mouse models, revealing multiple DEGs specifically associated with Tau or Aβ (Fig.1B ). The functional enrichment analysis revealed 36 GO terms enriched with DEGs altered in the PS2APP mice compared to WT. The most significantly enriched terms include processes such as "protein localization to cell periphery and plasma membrane", "interleukin−6 production and regulation", "exocytosis" and "neuron death" (Fig.1C ). For the comparison of the TauP301S mice versus WT controls, the functional enrichment analysis using DEGs revealed 95 terms. Among the most significantly enriched terms, we found "learning", "cognition", and "small GTPase mediated signal transduction" (Fig.1C ). Conclusion: Overall, we observed a small overlap of DEGs between the Aβ and tau mouse models, indicating the unique nature of GFAP‐positive astrocytic responses to different aspects of AD pathology. The findings presented in this study allowed the identification of functional categories and biological processes particular to Aβ or tau burden. Characterizing how these upstream triggers influence GFAP‐positive astrocyte phenotypes may contribute to the biological interpretation of GFAP as a biomarker of AD pathology and pave the way to unravel novel mechanisms and context‐specific astrocyte biomarkers for AD.